INVESTIGATING TEACHERS’ READINESS IN TEACHING INTEGRATED SOCIAL STUDIES: INDONESIAN CASES - Pupu Saeful Rahmat (Indonesian Journal of Learning and Instruction)
This research aims to find out: (1) how the readiness of teachers in Indonesia especially at  SMP Negeri 3 Kuningan, West Java  in teaching Integrated Social Studies in terms of the management of learning and (2) any constraints faced by Indonesian teachers in teaching Integrated Social Studies.  The method used in this research is qualitative method. The results showed that the readiness of Indonesia teachers in teaching Integrated Social Studies in terms of learning management of 80,15 % included in the ready category. Constraints faced by teachers in the field of teaching Integrated Social Studies, among others (1) Less united geography, economic, historical and sociological concepts in the minds of teachers (2) Limitations of supporting facilities of Integrated Social Studies learning at schools. Keywords:  teacher’s  readiness;  teaching;  integrated social studies.